For a Higher Sprint Running Performance, in Which Part of the Warm-Up Protocol Should the Dynamic Stretching Phase be Applied? - Recep Özçelik; Cem Bediz; Caner Çetinkaya; Erkan Günay; Egemen Mancı (Selcuk University, 2023)
The acute effect of warm-up protocols on athletic performance components has been frequently examined in the literature. The lack of evidence in static stretching studies led researchers to dynamic stretching protocols that simultaneously enhance basic skill level, kinesthetic awareness, range of motion, and core temperature. However, it was not clarified in which part of the warming up the dynamic stretching phase should be done. This study investigated the acute effect of the dynamic stretching exercise phase before and after a warm-up on the 20m sprint performance. The study included forty-four soccer players, aged 16.59 ±1.06 years, who played for amateur teams. Participants were randomly divided into two groups on the first day of the study. In the first group, dynamic stretching was performed before warm-up (BGW) and then the players' 20m sprint performances were tested. In the second group, dynamic stretching was performed after the warm-up (AGW) and then the players' 20m sprint performances were tested. On the second day of the study, the same protocol was applied to the same players by changing groups of players. The average speed in the 20m sprint test of the BGW group (2.96±0,13 sec.) was found to be significantly shorter than the AGW group (3.01±0,12 sec., p lt;0.05). The difference in the 20 m speed test values between groups was found significant (p lt;0.05). The findings obtained in the applied experimental condition show that the dynamic stretching protocol applied before the warm-up running phase increases the sprint running performance. It may be more beneficial for the performance of athletes to do dynamic stretching before sprint running performances.